Kompetensi Pengkajian Primary Survey dengan Pendekatan Metode Journal Sharing Of Critical Care (JSCC) pada Mahasiswa Profesi Ners - Heru Suwardianto; Vitaria Wahyu Astuti (Poltekkes Kemenkes Surakarta, 2020)
Background: Primary Survey is important to be achieved by nursing students in carrying out early detection of critical patient conditions. Innovation of learning methods is a challenge for teachers to improve the quality of student competencies. The research objective is the Primary Survey critical nursing competency with the method of journal sharing of critical care (JSCC) approach to nursing professional students. Methods: The research design is descriptive analytic. The study population was all professional students in 2020. The research sample was professional students in 2020 using total sampling. The size of the study sample was 39 respondents with the inclusion of students who had completed the medical surgical nursing profession and followed the critical nursing profession to completion. Primary Survey independent variable. Data were collected using a questionnaire and analyzed using data frequency distribution. Results: Showed that the most respondents had primary survey critical nursing competency values ​​obtained good value on the airway assessment of 53.8 respondents, breathing assessment of 56.4% of respondents, Circulation assessment of 61.5% of respondents, Disability assessment of 56.4 % of respondents, and Exprosure Assessment by 59% of respondents. Conclusion: The implementation of learning methods for journal sharing of critical care has a positive impact on student competencies to carry out primary survey assessments and produce good student competencies. It is not only the learning process that supports a competency but also the ability of students to follow the learning method.